Non-Royal Women at Serabit el-Khadim: Fact or Fiction?. (2nd January 2017) - Orlev, Nir
Abstract : At least 71 non-royal women are commemorated by name or image in the inscriptions and scenes at the temple of Serabit el-Khadim. Their representation at the site may lead to the conclusion that they were an integral part of the ancient Egyptian mining expeditions sent to Serabit el-Khadim during the second millennium BCE. However, analysis of the manner in which these women are mentioned proves that this is not the case; the women seem to be mentioned merely as family members of expedition personnel.